Hybrid Organic‐Inorganic Heterogeneous Interfaces for Electrocatalysis: A Theoretical Study of CO2 Reduction to C2. Issue 4 (2nd December 2021) - Wan, Mingyu; Gu, Zhiyong; Che, Fanglin
Abstract: Hybrid organic‐inorganic heterogeneous catalytic interfaces, where traditional catalytic materials are modified with self‐assembled monolayers (SAMs), create promising features to control a wide range of catalytic processes through the design of dual organic‐inorganic active sites and the induced confinement effect. To provide a fundamental insight, we investigated CO2 electroreduction into valuable C2 chemicals (CO2 RR‐to‐C2 ) over SAM‐modulated Cu. Our theoretical results show that 1/4 monolayer aminothiolates improve the stability, activity and selectivity of CO2 RR‐to‐C2 by: (1) decreasing surface energy to suppress surface reconstruction; (2) facilitating CO2 activation and C−C coupling through dual organic‐inorganic (i. e., −NH, Cu) active sites; (3) promoting C−C coupling via confinement effects that enlarge the adsorption energy difference between CO * and COH * ; (4) inducing local electric fields to Cu surface and changing its dipole moment and polarizability to be in favor of C−C coupling under electrode/electrolyte interfacial electric field. Abstract : CO2 RR‐to‐C2 : Aminothiolate self‐assembled monolayer (SAM)‐modulated Cu catalyst can: (1) provide dual active organic (amine) and inorganic (copper) sites within the confined space between organic‐inorganic interface and (2) induce local electric field and changes in surface dipole moments and polarizabilities. Taken together, it accelerates CO2 initial activation and C−C coupling, and thus promotes CO2 RR‐to‐C2 . This work leads to innovative electrocatalyst designs that promote organic‐inorganic active sites, confinement effects and highly localized electric fields, thus potentially enabling more efficient energy utilization and conversion efficiency than obtained with conventional catalyst designs.